Keragaman Wujud Bangunan Tinggal Desa-desa Bali Aga dari Zaman Bali Kuno - Ida Ayu Dyah Maharani (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
Some of ancient villages in Bali which to be known as Bali Aga villages, existed since Ancient Balinese era from 8th to 13th century. As a product which created from problem solving effort, Bali Aga's dwelling buildings still being learned today in generalized interpretation, as if it could represent dwelling building from all Bali Aga villages. This article aims to analyze the variation of the Bali Aga’dwelling buildings appearance and the factors behind. Through the synchronous and diachronic approach at several Bali Aga villages which are known from discoveries incription’s name from beginning to the end of Ancient Balinese era, it can be known, although it built from the same concept, there are some variation in its appearance which is determined by local believes, environmental and spirit of the era. At the beginning of the Ancient Balinese era, there was a home and house for residents as a place for all activities. The change from Ancient Bali to the Middle Bali periods showed the transition which brought about variations in the dwelling buildings.